Faktor-Faktor Yang Mempengaruhi Niat Berwirausaha Pada Mahasiswa S2 Di Universitas Di Jakarta Yang Mendapatkan Mata Kuliah Kewirausahaan - Christopher Arnold (Universitas Tarumanagara, 2019)
This study aims to determine the effect of attitudinal factor, bahavioral factor, and educational support on entrepreneur intention. Methods of data collection using questionnaires. The respondents of this research are postgraduate students of Universitas Tarumanagara, Universitas Atmajaya, Universitas Prasetiya Mulya, and Universitas BinaNusantara. The method of data analysis using multiple regression. The results of the study conclude that attitudinal factor, bahavioral factor, and educational factor have a positive effect on entrepreneur intention either partially or simultaneously. .